2022
DOI: 10.24940/theijbm/2022/v10/i3/bm2203-013
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of the Impact of Boko Haram Insurgency on Small and Medium Enterprises (SMEs) in Gombe State of Nigeria: Challenges and Prospects

Abstract: An Assessment of the Impact of Boko Haram Insurgency onSmall and Medium Enterprises (SMEs) in Gombe State of Nigeria: Challenges and Prospects IntroductionSince the early part of 2009, Nigerian government has been battling with insurgency caused by Boko Haram activities. Boko Haram is a religious based Nigerian Militant group that believe in extreme religious imposition of Sharia law in the northern states of Nigeria. Ideologically, the group opposes not only western education but also Western culture and mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…These are individuals who had no intention of starting a business but found that there was sufficient demand for their products or services. Second-career entrepreneurship encompasses the personal activities of these persons after their retirement (Lawal & Adeniran, 2022). The motivation for their involvement is usually to discuss the necessary shortfalls in the individual's income level after retirement or simply as a hobby to decrease unused time.…”
Section: Silver Entrepreneurshipmentioning
confidence: 99%
“…These are individuals who had no intention of starting a business but found that there was sufficient demand for their products or services. Second-career entrepreneurship encompasses the personal activities of these persons after their retirement (Lawal & Adeniran, 2022). The motivation for their involvement is usually to discuss the necessary shortfalls in the individual's income level after retirement or simply as a hobby to decrease unused time.…”
Section: Silver Entrepreneurshipmentioning
confidence: 99%
“…Another ecological factor impacting businesses is soil erosion, which negatively impacts agribusiness (Ugoani, 2020). A study showed that soil infertility, inadequate financing, and soil erosion are the major factors negating small agribusiness performance in Nigeria (Lawal et al, 2020). However, many ecological and environmental factors impact the performance of large and small businesses (Lampadarios, 2015).…”
Section: Ecological and Environmentmentioning
confidence: 99%